Factors of Purchase Decisions for Thrift Fashion Products Among Undergraduate Fashion Education Students - NI'MATUL MAULA; Agus Hery Supadmi Irianti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
The fast fashion industry reaps the threat of increasingly complicated environmental damage, and thrift fashion is one of the sustainable fashion statements that students favor because of its affordable price. The primary purpose of this study is to describe the factors of purchasing decisions for thrift fashion products for undergraduate students of Fashion Education and find out the dominant factors. The method used is descriptive quantitative, which describes each factor based on the percentage value. The data collection technique was done by distributing questionnaires online to 100 respondents of S1 Fashion Education Study Program students at the State University of Malang from 2018 to 2022 who purchased thrift fashion products. Based on the results of data processing, it is confirmed that cultural factors, social factors, personal factors, and psychological factors have a significant effect on thrift fashion purchasing decisions. Cultural factors contribute 25%, social factors 24%, personal factors 25%, and psychological factors 26%. So, the factor that dominates purchases is psychological factors. This analysis is expected to be a reference for marketers to determine a more effective strategy. It is also valuable to the literature regarding thrift fashion consumption trends and sustainable fashion campaigns.